2014
DOI: 10.12968/ajmw.2014.8.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women's awareness of antenatal danger signs and birth preparedness in rural Gambia

Abstract: Aim: The objectives of this study were to explore pregnant women's awareness of antenatal danger signs and birth preparedness as well as to identify associated factors in rural Gambia. Methods: A clinic-based cross-sectional study design was conducted at seven public health centres in rural Gambia involving a convenience sample of 145 pregnant women attending antenatal care services. Results: The study revealed that 61% of the pregnant women interviewed were aware of antenatal danger signs. In step wise multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…To account for this, the trim and fill metaanalysis found that only 25.2% (95% CI: 20.0, 30.6%) were well prepared for birth and related complications by practicing elements of BPCR. Our finding is higher than studies done in the rural Gambia (14%) and Kenya [48,49]. Discrepancies may be due to Ethiopia's flexible initiatives over time to bring more attention to the issue.…”
Section: Discussioncontrasting
confidence: 86%
“…To account for this, the trim and fill metaanalysis found that only 25.2% (95% CI: 20.0, 30.6%) were well prepared for birth and related complications by practicing elements of BPCR. Our finding is higher than studies done in the rural Gambia (14%) and Kenya [48,49]. Discrepancies may be due to Ethiopia's flexible initiatives over time to bring more attention to the issue.…”
Section: Discussioncontrasting
confidence: 86%
“…This finding is relatively similar to the study conducted in Uganda (35%) [ 39 ]. But it was Higher than a study carried out in Gambia (14%) [ 40 ]. In contrast, it is lower than studies carried out in West Bengal, India (57%) [ 41 ], Dehli, India (41%) [ 4 ] and Osun State, Nigeria (61%) [ 42 ].This difference might be due to socio-cultural issues like use of traditional birth attendant, women’s educational, economical status and the difference in implementation of prenatal health programs like quality of antenatal care services.…”
Section: Discussionmentioning
confidence: 56%
“…However, the outcome in this review is better compared with the meta-analysis carried out in Ethiopia which nd he he is at is he ch reported that only one-thirds of pregnant women in Ethiopia were prepared for birth and its complication 15 . Also, it is higher than the studies carried out in Uganda, Bangladesh 18 and Gambia 19 . In contrast, it is lower than the studies conducted in Accra 20 .…”
Section: Discussionmentioning
confidence: 56%